2 x + y =5 3 x + 2 y=15
pablogoudeltavares:
é 53 x ali
Respostas
respondido por:
2
3 x + 2 y = 15 (i)
2 x + y = 5 (ii) Isolando o y no 1º membro ------> y = 5 - 2 x (iii) e substituindo em (i) temos:
3 x + 2 .( 5 - 2 x) = 15 ------> 3 x + 10 - 4 x = 15 ------> - x = 15 - 10 ⇒ - x = 5 ---------> x = - 5 . Substituindo em (iii) temos y = 5 - 2 .(-5) ------> y = 5 + 10 ⇒ y = 15
Resposta: x = - 5 e y = 15 S = {( - 5 , 15 )} Jóia?
2 x + y = 5 (ii) Isolando o y no 1º membro ------> y = 5 - 2 x (iii) e substituindo em (i) temos:
3 x + 2 .( 5 - 2 x) = 15 ------> 3 x + 10 - 4 x = 15 ------> - x = 15 - 10 ⇒ - x = 5 ---------> x = - 5 . Substituindo em (iii) temos y = 5 - 2 .(-5) ------> y = 5 + 10 ⇒ y = 15
Resposta: x = - 5 e y = 15 S = {( - 5 , 15 )} Jóia?
respondido por:
0
Método da Adição:
2x + y = 5 ( - 2)
3x + 2y = 15
- 4x - 2y = - 10
3x + 2y = 15 (+)
- x = 5 ( - 1)
x = - 5
2x + y = 5
2.(- 5) + y = 5
- 10 + y = 5
y = 5 + 10
y = 15
R.: x = - 5 e y = 15
2x + y = 5 ( - 2)
3x + 2y = 15
- 4x - 2y = - 10
3x + 2y = 15 (+)
- x = 5 ( - 1)
x = - 5
2x + y = 5
2.(- 5) + y = 5
- 10 + y = 5
y = 5 + 10
y = 15
R.: x = - 5 e y = 15
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás